Hubungan antara Trait Kepribadian Neuroticism dan Self-Regulated Learning pada Siswi Pondok Pesantren “X” di Yogyakarta - Ike Zuraeni; Sara Palila (UIN Sunan Kalijaga, 2016)
This study aims to investigate the correlation between personality trait Neuroticism and Self Regulated Learning on student at Pondok Pesantren